Pembelajaran Sejarah Kebudayaan Islam dalam Meningkatkan Toleransi Beragama Siswa pada Jenjang Pendidikan Dasar - Rizal, Syaiful (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2021)
Abstract God sent down and created various religions on earth with the aim of saving people and their lives from damage. This diversity is not a barrier and a barrier for humans to do good, get to know and help, but as a treasure and a blessing so that human life is dynamic and not monotonous. The purpose of the Islamic Cultural History Subject is to develop education optimally through history, create and build young generations who emulate the struggles and achievements of Islamic heroes in defending and spreading Islam, and students take lessons from history and make history as a record in individuals for life. everyday life and use it in the present. Teachers who are actually at the forefront of teaching learning, especially religion teachers or teachers of Islamic cultural history, need to focus on the value of religious tolerance. Because in this world there is no single religion that teaches enmity between other religions, blames other religions and even judges other religions. everything teaches mutual respect and respect for each other's beliefs. Keywords: Islamic Cultural History, Religion, Tolerance